A visual detection films based on waterborne polyurethane for real-time monitoring of yogurt freshness. (February 2023) - Guo, Jing; Zhang, Hongjuan; Chen, linguo; Ding, Lei; Hu, Fan; Pei, Liujun; Liang, Shuaitong; Yang, Qun; Wang, Jiping
Abstract: Intelligent packaging has been becoming an innovative tool to provide information on the safety of food. A new pH sensor film based on waterborne polyurethane (WPU) incorporated with heterocyclic azo reactive dye was developed. FT-IR, TGA, and WCA analysis was used to characterize the properties of modified WPUs. It was demonstrated that the thermal stability and mechanical properties of WPUs film increased slightly after dye modification. The pH sensing results indicated that the pH sensor film showed an apparent color change from red to brown and finally to green in response to pH changes, and excellent reversibility when pH was varied between 3 and 10. Additionally, the pH sensor films also showed a remarkable resistance to leakage property under strong acidic and alkaline solutions. As a result, when applied to different kinds of fresh yogurt, an obvious color change from atrovirens to red was observed. Besides, the color sensor film showed reusable and stable performance. This study suggested that the prepared pH sensor film can be used as a part of an intelligent packing system for real-time freshness monitoring of yogurt products. Highlights: A new pH sensor film based on waterborne polyurethane (WPU) incorporated with heterocyclic azo reactive dye was developed. The pH sensor film showed an apparent color change and excellent reversibility. The pH sensor films also showed a remarkable resistance to leakage property under strong acidic and alkaline solutions. pH sensor film can be used as a part of an intelligent packing system for real-time freshness monitoring of yogurt products.